2007
DOI: 10.1371/journal.pone.0000928
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical DNA Repair and Peroxide Resistance Gene Conservation in Bacillus pumilus SAFR-032

Abstract: Background Bacillus spores are notoriously resistant to unfavorable conditions such as UV radiation, γ-radiation, H2O2, desiccation, chemical disinfection, or starvation. Bacillus pumilus SAFR-032 survives standard decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility, and both spores and vegetative cells of this strain exhibit elevated resistance to UV radiation and H2O2 compared to other Bacillus species.Principal FindingsThe genome of B. pumilus SAFR-032 was sequenced and annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 71 publications
3
110
1
3
Order By: Relevance
“…Endospores of B. pumilus SAFR-032 are resistant to high concentrations of H 2 O 2 (5% for 60 min) and simulated Martian UV irradiation (29,38). The SAFR-032 genome was sequenced, and numerous protein-encoding genes were identified as putative candidates responsible for the strain's enhanced resistance to the various sterilization treatments tested (21). Understanding its hydrogen peroxide resistance is particularly important since H 2 O 2 is used in current and newly developed sterilization methods (29,46).…”
mentioning
confidence: 99%
“…Endospores of B. pumilus SAFR-032 are resistant to high concentrations of H 2 O 2 (5% for 60 min) and simulated Martian UV irradiation (29,38). The SAFR-032 genome was sequenced, and numerous protein-encoding genes were identified as putative candidates responsible for the strain's enhanced resistance to the various sterilization treatments tested (21). Understanding its hydrogen peroxide resistance is particularly important since H 2 O 2 is used in current and newly developed sterilization methods (29,46).…”
mentioning
confidence: 99%
“…UVR-resistant microorganisms have shown tremendous stable biotechnological implications [2,3,29,30]. The short exposure of UV is generally known for random mutagenesis, however microbial reversion may produce unstable mutants with commercially viability.…”
Section: Occurrence Of Microorganisms At Higher Altitudes and Uvrmentioning
confidence: 99%
“…[32]. Gioia et al [29] have reported several genes involved in DNA repair and oxidative stress (dinG, disA, dnaE, mutL, ogt, pcrB, polA, polY2, recD, sms, uvrX, uvrA, uvrB, sodA, sodF, bcrC, and many more caused by UV-C radiation). Two novel species of Bacillus, B. nealsonii, isolated from a spacecraft assembly facility, and B. odysseyi, were resistant to UV radiation [39,40].…”
Section: Tolerance and Survivability Of Uvrresistant Extremophilesmentioning
confidence: 99%
“…The bacterial species surviving highly unfavorable conditions have always been enigmatic to the scientifi c world and can provide a lot of interesting information regarding genes and factors which facilitate them to do so. Bacillus pumilus SAFR-032 is one such organism that produces spores highly resistant to unfavorable conditions like UV radiation, gamma-radiation, oxidative stress, desiccation, chemical disinfection, or starvation and have been sequenced by Baylor College of Medicine [47]. Both the vegetative cells and the spores of this strain are found to be more resistant to UV and H 2 O 2 as compared to other Bacillus species and it even survives the decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility.…”
Section: Revealing Extreme Livingmentioning
confidence: 99%
“…Its 3.7 Mb genome 3687 ORFs, 12 frameshifts, 38 pseudogenes, 7 rRNA operons, 69 tRNAs, and 21 ncRNAs. The whole genome data also revealed many genes relevant to DNA repair and the oxidative stress response and those were then compared to the less resistant bacillus species B. subtilis and B. licheniformis [47]. The B. pumilus genome includes genes not found in B. subtilis or B. licheniformis and conserved genes with sequence variations, but surprisingly lacks several genes that function in UV or H 2 O 2 resistance in other Bacillus species.…”
Section: Revealing Extreme Livingmentioning
confidence: 99%